2022
DOI: 10.1007/s42107-022-00509-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of covid-19 on supply chain management in construction industry in Kashmir

Abstract: The building industry has become a critical economic sector for country’s development. Due to covid-19, world’s most industrialised countries saw significant declines in their GDP. An effective supply chain system ensures higher efficiency rates, better customer relationship and service, reduced production costs and an overall improvement in the financial performance of a construction company. The entry of covid-19 in Kashmir has adversely impacted the supply chain of construction industry and the economy. So,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The COVID-19 pandemic has posed distinctive challenges for the housing industry, ushering in uncertainties regarding market demand, pricing, and consumer inclinations (Zeng & Yi, 2022). Stakeholders must grapple with evolving house preferences to ensure their offerings resonate with potential homebuyers while contending with potential disruptions in construction and supply chains (Farooq et al, 2022). Recognizing these challenges is pivotal for devising strategies to navigate risks effectively.…”
Section: Covid-19 Impact On Property Sectormentioning
confidence: 99%
“…The COVID-19 pandemic has posed distinctive challenges for the housing industry, ushering in uncertainties regarding market demand, pricing, and consumer inclinations (Zeng & Yi, 2022). Stakeholders must grapple with evolving house preferences to ensure their offerings resonate with potential homebuyers while contending with potential disruptions in construction and supply chains (Farooq et al, 2022). Recognizing these challenges is pivotal for devising strategies to navigate risks effectively.…”
Section: Covid-19 Impact On Property Sectormentioning
confidence: 99%
“…The disruptions induced by COVID-19 have been addressed in various studies, highlighting the need to model the impacts of COVID-19 in supply chain activities and to assess supply chain resilience to the outbreak of COVID-19 in different industries (Karuppiah et al, 2022;Badhotiya et al, 2022;Farooq et al, 2022). The pandemic has also affected the food supply chain, leading to discussions on the implications of COVID-19 on socioeconomic factors and the impact of lockdown on the food supply chain and agri-business (Barman & De, 2021).…”
Section: Supply Chain Analytics and Factors Affecting Itmentioning
confidence: 99%

The Impact of COVID-19 on supply chain analytics: A global review

Bankole Ibrahim Ashiwaju,
Israel Osejie Okoduwa,
Jeremiah Olawumi Arowoogun
et al. 2024
World J. Adv. Res. Rev.
“…A critical analysis of the 54 PPGCI articles reviewed in this paper revealed that four distinct PP themes were investigated, and these are presented in Figure 3. that Covid-19 had a significant negative impact on project performance in the construction industry, with the main impacts being reduced worker productivity (Al-Mhdawi et al, 2023;Oni et al, 2023;Wijayaningtyas et al, 2022), scarcity and cost increases of building materials due to supply chain disruptions (Alhammadi, 2022;Farooq et al, 2022;Gumusburun Ayalp & Çivici, 2022) and poor cash flows due to scarcity of construction projects during the pandemic (Oladimeji, 2022;Sami Ur Rehman et al, 2022;Tekin, 2022).…”
Section: Themes Investigated By Ppgci Articles During the Covid-19 Er...mentioning
confidence: 99%